2009
DOI: 10.1089/neu.2008-0794
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapies for Traumatic Brain Injury – Prospective Considerations

Abstract: Traumatic brain injury (TBI) initiates a cascade of numerous pathophysiological events that evolve over time. Despite the complexity of TBI, research aimed at therapy development has almost exclusively focused on single therapies, all of which have failed in multicenter clinical trials. Therefore, in February 2008 the National Institute of Neurological Disorders and Stroke, with support from the National Institute of Child Health and Development, the National Heart, Lung, and Blood Institute, and the Departmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
152
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(152 citation statements)
references
References 115 publications
(138 reference statements)
0
152
0
Order By: Relevance
“…185,188,189 Potentially, hypothermia impedes the progression of TAI, allowing adjunct drug therapy to superimpose protective effects at more delayed time points. Regardless, combinational therapy with hypothermia merits continued investigation.…”
Section: Hypothermiamentioning
confidence: 99%
“…185,188,189 Potentially, hypothermia impedes the progression of TAI, allowing adjunct drug therapy to superimpose protective effects at more delayed time points. Regardless, combinational therapy with hypothermia merits continued investigation.…”
Section: Hypothermiamentioning
confidence: 99%
“…The overall lack of translational success has evolved into the current thinking by many in the TBI community that mono-therapies may be insufficient to produce a translatable product, and that a more dedicated effort toward poly-therapies is necessary. Indeed, a National Institutes of Health (NIH) TBI workshop convened to discuss the opportunities and challenges associated with conducting research studies using multiple drug interventions (Margulies et al, 2009). The workshop leaders focused exclusively on the potential for combinatorial pharmacological agents to promote recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these efforts, mortality for TBI patients in emergency care facilities remains between 25% and 30% (Tu et al, 2012), and no successful Phase III trials of pharmacological agents for TBI have been reported to date (Okonkwo, 2008). Because of the increasing prevalence and high mortality rate of TBI (Margulies and Hicks, 2009), improved early diagnostic methods and treatment strategies for TBI are urgently required in clinical settings, posing a challenge for neurological researchers.…”
Section: Introductionmentioning
confidence: 99%